2015
DOI: 10.1080/01635581.2015.1004591
|View full text |Cite
|
Sign up to set email alerts
|

Natural Grape Extracts Regulate Colon Cancer Cells Malignancy

Abstract: Natural dietary components are evolutionary-selected molecules able to control inflammation and cancerous transformation and progression. Because many studies assessed the beneficial properties of key molecules extracted from grapes, we aimed at investigating the properties of Liofenol™, a natural red wine lyophilized extract, devoid of alcohol and composed by a miscellaneous of components (polyphenols, flavonoids, anthocyanins). We proved that the colon cancer cell line HCT116 responded to Liofenol™ treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 53 publications
(70 reference statements)
0
23
0
1
Order By: Relevance
“…26,27 In animal models, resveratrol has also been shown to prevent the formation of colon tumors via down-regulation of genes involved in cell cycle progression genes, 28 inhibit the growth of implanted human primary gastric cancer cells 29 and enhance the anti-tumor effect of 5-fluorouracil on H22 murine hepatoma. 30 Other studies of red wine extract have suggested that the polyphenolic compounds in red wine induce an antioxidant response and reduce proliferation in colon cancer cell lines 31,32 and in mouse models of colon cancer. 33 Human studies into the association between wine consumption and cancer outcomes have been limited.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In animal models, resveratrol has also been shown to prevent the formation of colon tumors via down-regulation of genes involved in cell cycle progression genes, 28 inhibit the growth of implanted human primary gastric cancer cells 29 and enhance the anti-tumor effect of 5-fluorouracil on H22 murine hepatoma. 30 Other studies of red wine extract have suggested that the polyphenolic compounds in red wine induce an antioxidant response and reduce proliferation in colon cancer cell lines 31,32 and in mouse models of colon cancer. 33 Human studies into the association between wine consumption and cancer outcomes have been limited.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols have also been implicated in many other chronic conditions such as Parkinson disease, Alzheimer's disease, antinociceptive, immune response, malignancy, anticalcification, hypertension, health and development, etc. Srinivasan and Lahiri 2015;Rahman et al 2015;Magrone and Jirillo 2015;Signorelli et al 2015;Wang et al 2015;Teles et al 2015;Ly et al 2015). There is a plethora of information that reflects on the fact that activities of green tea polyphenolic compounds can control chronic diseases that are mediated through persistent inflammation.…”
Section: Green Tea Has Anti-inflammatory and Anticancer Propertiesmentioning
confidence: 99%
“…Furthermore, evidence has been provided that muscadine grape skin extract was able to induce an unfolded protein response-mediated autophagy with apoptosis of prostate cancer cells [206]. In this framework, Liofenol™ a RWE enriched in polyphenols, reduced colon cancer cell growth with an increase in p53 and p21 protein expression [207]. Polyphenol effects on cancer are summarized in Table 6.…”
Section: Cancermentioning
confidence: 99%
“…Suppression of angiogenesis and induction of apoptosis, reduction of pre-cancerous lesions [203][204][205] Muscadine grape skin extract Prostate cancer Induction of autophagy with apoptosis of cancer cells [206] Liofenol TM (RWE) Colon cancer cells Arrest of cell growth with increase in p53 and p21 protein expression [207] Abbreviations: EGCG, epigallocatechin gallate, IFN, interferon, IL, interleukin, RES, resveratrol, RWE, red wine extracts, STAT, signal transducer and activator of transcription, TAM, tumor associated macrophages, TGF, transforming growth factors, Treg, T regulatory cells.…”
Section: Rwe Murine Cancermentioning
confidence: 99%